Terrorist financing and perceptions on islamic financial institutions / Normah Omar. - Omar, Normah (Universiti Teknologi MARA Cawangan Selangor, 2010)
The terrorist attacks of the United States (US) World Trade Center on September 11, 2001; Bali bombings in 2002 and 2005; London Bombing in 2005; and the Mumbai bombing in 2008 had left some very detrimental global perceptional impacts on the Muslims and Islamic financial institutions globally. As most of these attacks were carried out by some militant Islamicists, understandably there were a lot of public skepticism against the Muslims and the religion of Islam. In the United States of America (USA) for example, following the attacks on September 11, the US government enacted the USA PATRIOT Act, which is basically designed to prevent the use of the US financial system to help fund terrorism and other crimes. The enactment of the PATRIOT Act 2001 had accelerated the establishment of similar laws globally. In Malaysia particularly, the Anti Money Laundering and Anti-Terrorism Financing Act was introduced in 2001 and amended in 2007 to include more emphasis on the terrorist financing aspects. By virtue of these Acts, terrorist financing is a criminal offence. To date, most writings implicating Islamic financial institutions with terrorist financing are either written by Western authors or the articles are perceptional in nature. This conceptual paper reviews previous studies on this topic, examines related legislations, progresses to propose research strategies on how to counter these perceptional biases and highlights preventive mechanisms adopted by the Malaysian Islamic financial institutions in mitigating and detecting terrorists financing.